2009
DOI: 10.1186/1471-2229-9-116
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of S-adenosylmethionine-dependent halide/thiol methyltransferase (HTMT) in methyl halide emissions from agricultural plants: isolation and characterization of an HTMT-coding gene from Raphanus sativus (daikon radish)

Abstract: Background: Biogenic emissions of methyl halides (CH 3 Cl, CH 3 Br and CH 3 I) are the major source of these compounds in the atmosphere; however, there are few reports about the halide profiles and strengths of these emissions. Halide ion methyltransferase (HMT) and halide/thiol methyltransferase (HTMT) enzymes concerning these emissions have been purified and characterized from several organisms including marine algae, fungi, and higher plants; however, the correlation between emission profiles of methyl hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…OsHOL1 and OsHOL2 belong to Cluster IV, together with other HOL proteins of monocotyledonous plants. OsHOL2 was more similar to HOL proteins of the other monocots than OsHOL1.e Rice Expression Pro le Database (RiceXPro; http:// ricexpro.dna.a rc.go.jp) (Sato et al 2010) showed that OsHOL1 is expressed mainly in the leaf blade, whereas OsHOL2 is expressed in the whole plant at lower levels than OsHOL1 (data not shown), implying their di erent physiological roles.Whereas methyltransferase activity toward iodide ions had been reported in crude extract prepared from rice tissues (Itoh et al 2009), it was not examined whether OsHOL1 and OsHOL2 possess SAMdependent methyltransferase activities toward iodide ions. Therefore, we first examined whether OsHOL1 and OsHOL2 have the activity toward iodide ions as well as bromide, chloride, and thiocyanate ions.…”
mentioning
confidence: 99%
“…OsHOL1 and OsHOL2 belong to Cluster IV, together with other HOL proteins of monocotyledonous plants. OsHOL2 was more similar to HOL proteins of the other monocots than OsHOL1.e Rice Expression Pro le Database (RiceXPro; http:// ricexpro.dna.a rc.go.jp) (Sato et al 2010) showed that OsHOL1 is expressed mainly in the leaf blade, whereas OsHOL2 is expressed in the whole plant at lower levels than OsHOL1 (data not shown), implying their di erent physiological roles.Whereas methyltransferase activity toward iodide ions had been reported in crude extract prepared from rice tissues (Itoh et al 2009), it was not examined whether OsHOL1 and OsHOL2 possess SAMdependent methyltransferase activities toward iodide ions. Therefore, we first examined whether OsHOL1 and OsHOL2 have the activity toward iodide ions as well as bromide, chloride, and thiocyanate ions.…”
mentioning
confidence: 99%
“…Homologues of this enzyme have been found in several organisms, such as higher plants (Attieh et al 2000;Itoh et al 2009), algae (Itoh et al 1997), fungi, and soil bacteria (Amachi et al 2001) In this study, various marine phytoplankton were cultivated in order to clarify the molecular formation mechanism of methyl halides and to establish a correlation between intracellular halide ion methyl transferase/halide ion thiol methyl transferase (HTM/HTMT) activity and CH 3 X emission. The enzyme genes were isolated from marine phytoplankton, verified, expressed in E. coli, and characterized in detail.…”
Section: Elucidation Of the Mechanism Of Methylmentioning
confidence: 99%
“…Experimental details for strains, cultivation of phytoplankton, analytical conditions of GC-MS, enzyme assay, preparation of genomic DNA, plasmid construc- tion, and expression and purification of recombinant enzymes are described in Itoh et al (2009) and Toda and Itoh (2010).…”
Section: Elucidation Of the Mechanism Of Methylmentioning
confidence: 99%
See 2 more Smart Citations